2020
DOI: 10.1590/1414-431x20198917
|View full text |Cite
|
Sign up to set email alerts
|

Anti-placental growth factor antibody ameliorates hyperoxia-mediated impairment of lung development in neonatal rats

Abstract: This study investigates the effect of the overexpression of the placental growth factor (PGF) and hyperoxia on lung development and determines whether anti-PGF antibody ameliorates hyperoxia-mediated impairment of lung development in newborn rats. After exposure to normoxic conditions for seven days, newborn rats subjected to normoxia were intraperitoneally or intratracheally injected with physiological saline, adenovirus-negative control (Ad-NC), or adenovirus-PGF (Ad-PGF) to create the Normoxia, Normoxia+Ad-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Abnormal lipid metabolism in CF HBEC correlated with enhanced shedding of cytokines and growth factors to the basal medium ( Table 2 , Supplementary Table S1 ). The data highlight the enhanced inducible cytokine CXCL5 involved in neutrophil recruitment, tissue remodeling and COPD ( Chen et al, 2019 ), and placental growth factor (PGF) which is induced in the lung hyperoxia response, involved in macrophage polarization and angiogenesis, and exacerbates pulmonary fibrosis ( Zhao et al, 2019 ; Zhang et al, 2020 ). Both proteins correlated with oxidative stress markers, inflammation, and lung CT scores in CF infant BALF ( Horati et al, 2020 ), consistent with a role of these epithelial factors in early CF lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal lipid metabolism in CF HBEC correlated with enhanced shedding of cytokines and growth factors to the basal medium ( Table 2 , Supplementary Table S1 ). The data highlight the enhanced inducible cytokine CXCL5 involved in neutrophil recruitment, tissue remodeling and COPD ( Chen et al, 2019 ), and placental growth factor (PGF) which is induced in the lung hyperoxia response, involved in macrophage polarization and angiogenesis, and exacerbates pulmonary fibrosis ( Zhao et al, 2019 ; Zhang et al, 2020 ). Both proteins correlated with oxidative stress markers, inflammation, and lung CT scores in CF infant BALF ( Horati et al, 2020 ), consistent with a role of these epithelial factors in early CF lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…CD34 + cells maintain tissue homeostasis [71] and are activated during tissue injury, increasing the expression of growth repair tissue factors such as Areg [72]. CD34 is also an angiogenic marker, and HO exposure has dual effects on the expression of this protein [73,74]. Our findings indicate that HO but not Areg increases CD34 expression in fetal murine lung ECs.…”
Section: Discussionmentioning
confidence: 66%
“…PlGF is a member of the VEGF family and is minimally expressed in the mature lung under homeostatic conditions. 47,48 This cytokine has been studied most commonly in pathologic lung diseases, such as bronchopulmonary dysplasia, 49,50 lung cancer, [51][52][53][54] and hyperoxia-induced lung injury. 50,55 More recently, investigators have identified PlGF as a key signaling cytokine in hepatopulmonary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 This cytokine has been studied most commonly in pathologic lung diseases, such as bronchopulmonary dysplasia, 49,50 lung cancer, [51][52][53][54] and hyperoxia-induced lung injury. 50,55 More recently, investigators have identified PlGF as a key signaling cytokine in hepatopulmonary syndrome. 56,57 Unlike VEGF-A, which regulates angiogenesis in homeostasis as well as during lung development, PlGF exclusively regulates angiogenesis in pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%